738 Introducing a cooling pathway to improve first aid of burns in the emergency department. (17th August 2022) - Picton, Aled; Ikhlaq, Zanum; Kanani, Anand
Abstract : Aims: Background: Effective first aid for burns is proven to improve patient outcomes, including burn severity.(1) British Burn Association guidance defines effective first aid as 'cooling' with twenty minutes of cool running water, provided within three hours of injury.(2) Objectives: To improve the clinical outcomes for patients presenting to a paediatric emergency department (PED) with burns through the design, implementation and evaluation of a cooling pathway. Methods: To obtain pre-intervention data, a retrospective review of the electronic records of patients who presented to our institution with burns between May - June 2020 was conducted. Inclusion criteria: triage time <3 hours from injury, clear documentation of time of injury and first aid provided. Key exclusion criteria: reattendance, transfer from another hospital, incomplete documentation. A multidisciplinary stakeholder team designed a cooling pathway. Children deemed eligible for cooling were those presenting to PED <3 hours after their burn who had received either no first aid or <20 minutes of cool running water. Cooling was initiated after the patient was assessed by a member of the PED team, either at triage or when brought into a bedspace by an ambulance crew. Cooling was provided using a sink or shower. The pathway was introduced in July 2020. Immediate post-intervention data for eligible patients who presented between July - September 2020 was collected. Finally, we collected follow-up data for eligible patients who presented in December 2021. All three datasets used the same inclusion and exclusion criteria. Results: See table 1 . Pre intervention: Electronic records for 158 patients were screened. Cooling would have been indicated for 44 patients. Of these, 22 patients (50%) had already received effective first aid at home. The remaining 22 (50%) were eligible for cooling in the PED, but only 3 patients (14%) received this. Post intervention: Electronic records for 143 patients were screened. Cooling was indicated for 52 patients. Of these, 21 (41%) patients had already received effective first aid at home. Of the remaining 31 patients, 24 (77%) received cooling in the PED. No families declined cooling. Follow up dataset: Electronic records for 58 patients were screened. Cooling was indicated for 15 patients. All eligible patients (15, 100%) received cooling in the PED. Conclusion: Before the project, first aid delivery was ad hoc and opportunities to improve burn outcomes were missed. We introduced a standardised cooling pathway to bring our burns first aid in line with national guidance. The intervention was acceptable to families, cost-neutral and evidence-based. Posters and staff provided consistent messaging to families about burns first aid, which may improve future provision of effective first aid at home. Cooling was largely initiated at triage, ensuring timely first-aid and a smooth patient journey through the department. Introducing the pathway has led to a sustained improvement in provision of effective first aid for patients presenting to our institution with burns. References: Wood FM et al. Water First Aid Is Beneficial In Humans Post-Burn: Evidence from a Bi-National Cohort Study . PLoS ONE 2016; 11(1):e0147259. British Burn Association. First Aid Clinical Practice Guidelines (2018).